Analisis Konstruksi Jembatan Busur Rangka Baja Tipe A-half Through Arch - Olyvia, Yumna Cici; Bayzoni, Bayzoni; Purwanto, Eddy (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Indonesia is an archipelago and has an important role connecting bridges between islands . Theneed for long -span bridges and lightweight materials and consist artistic value , then the arc steeltruss bridge is an alternative of the problem. In this research will focus on the type a half througharc.The bridge is design to 120 m,span and 12 m,height with a transverse dimension of thevehicle floor complete with sidewalk is 11 m to 2 lanes 2 -way with pavement width of 1 m .Loading calculations used in the planning of the bridge is based on the regulation BMS 1992 andRSNI T - 02-2005 and calculation of the power structure refers to RSNI T - 03-2005 and SNI 03-1729-2002.The results of the study are obtained composite vehicle floor plates , with a reinforced concreteslab thickness of 250 mm . Transverse girder and longitudinal girder using iwf.900.300.28.16iwf.400.200.13.8 with BJ 55. The connection between the ransverse girder and longitudinal girderusing bolts with A325 quality with a diameter of 25 mm with 10 mm thick plate BJ 34. The mainstructure of the arc in the form iwf.400.400 .21.13 . The main structure connection using bolts withA325 quality with a diameter of 35 mm with 2 5 mm thick plate BJ 5 0 .Keywords : bridge , A - Half Through Arch , steel